Diseño de estrategias para la mejora de la atención ginecobstétrica en los hospitales del Atlántico (2020)
Gynecobstetrics departments (GDs) are in charge of diagnosing, monitoring, and treating female reproductive diseases as well as assisting women during pregnancy. Their importance motivates the creation of suitable performance evaluation approaches for identifying weaknesses and designing focused interventions. Therefore, the aim of this paper is two-fold: i) provide an approach for GD performance evaluation and ii) propose interventions tackling the GDs’ weaknesses.The implemented approached for evaluating the overall performance of DGs is a Hybrid decision making model based on FAHP, DEMATEL and TOPSIS. The Fuzzy Analytic Hierarchy Process (FAHP) was first applied to calculate the initial criteria and sub-criteria weights under vagueness. Then, the Decision-Making Trial and Evaluation Laboratory (DEMATEL) was implemented to evaluate interrelations. FAHP and DEMATEL were later combined to estimate the final criteria and sub-criteria weights under vagueness and interdependency. Finally, the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) was used to rank the GDs and detect improvement opportunities. Finally, a case study of a cluster including three GDs is presented to validate the proposed approach, in which performance comparisons were made and the weak points were identified for each GD. From a literary review, the possible causes separating these DGs from the desired performance were identified, and action plans were constructed aimed to improve the healthcare cluster performance.